2014
DOI: 10.1371/journal.pntd.0003030
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Japanese Encephalitis in Taiwan—A Population-Based Study

Abstract: BackgroundA mass Japanese encephalitis (JE) vaccination program targeting children was launched in Taiwan in 1968, and the number of pediatric JE cases substantially decreased thereafter. The aim of this study was to elucidate the long-term trend of JE incidence, and to investigate the age-specific seroprevalence of JE-neutralizing antibodies.Methodology/Principal FindingsA total of 2,948 laboratory-confirmed JE cases that occurred between 1966 and 2012 were analyzed using a mandatory notification system manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(84 citation statements)
references
References 31 publications
6
77
1
Order By: Relevance
“…The age of JE occurrence shifted from a younger age group to an older age group. Similar to the results of a previous study, 7 this study found that the number of JE cases reported between 2000 and 2014 in Taiwan was far below that of the pre-vaccination era, when at least 5-15 times more cases were reported annually (the average number of JE cases reported in 1968 was 200). 6 The incidence of JE was higher among people 20 years or older than it was among those under 20 years.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The age of JE occurrence shifted from a younger age group to an older age group. Similar to the results of a previous study, 7 this study found that the number of JE cases reported between 2000 and 2014 in Taiwan was far below that of the pre-vaccination era, when at least 5-15 times more cases were reported annually (the average number of JE cases reported in 1968 was 200). 6 The incidence of JE was higher among people 20 years or older than it was among those under 20 years.…”
Section: Discussionsupporting
confidence: 89%
“…We did an advanced analysis and found the incidence rates of JE increased as age increased, with a peak incidence rate in the age group of 40-59 years. The previous study 7 shows that the positive rates of JE neutralizing antibodies in Taiwanese people were 74%, 63%, 55%, 54%, 68%, and 86% among 1981-1986, 1976-1980, 1970-1975, 1963-1969, and 1912-1952 cohorts, respectively. The countries neighboring Taiwan have confronted similar problems, with the majority of JE cases shifting from children to adults.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations